Public Works of Manuel Fresco’s Government in Buenos Aires Province - Cristina Ambrosini (Perspectivas Metodológicas​)
In this article, we refer to the recently published book, edited by Dr. Aritz Recalde, entitled Public Works of Manuel Fresco’s Government in Buenos Aires Province, Remedios de Escalada, National University of Lanús, 2025. We begin by highlighting the boldness and commitment of this research, given the complexity of the politician at the center of this study, as he belongs to the 1930s in Argentina, known as "the infamous decade," marked by the crisis of the interwar period. Following the presentation of this comprehensive report on Governor Fresco's four-year administration of the Province of Buenos Aires, we will refer to the radio report in which Recalde expresses his views on the value of this work and the need to provide knowledge, in the field of National Thought, on the public works of this and other governors, since there is a lack of writings on these politicians who, at key moments in the history of our country, have assumed the management of a province that is decisive for the political life of Argentina.